Frequency and duration of suffering of cervical cancer patients and caregivers: Results from an international Delphi study - Xiaoxiao Jiang Kwete; Khadidjatou Kane; Yuwei (Alyssa); Eric L. Krakauer (Public Library of Science (PLoS), 2023)
This paper describes a Delphi process executed between August and September, 2020, to identify types of physical, psychological, social and spiritual suffering and their severity, prevalence and duration associated with cervical cancer to enable estimation of the global and regional palliative care needs of these cervical cancer patients and their family caregivers. Patients were dichotomized into decedents (those who died of cervical cancer in any given year) and non-decedents (those who had cervical cancer in any given year but did not die in that year). A two-round web-based Delphi study was conducted using a panel of 12 experts with first-hand experience taking care of cervical cancer patients and their family caregivers, two from each World Health Organization (WHO) region. We identified thirteen types of physical suffering, six psychological types, three social types and three spiritual types. Frequencies and durations were given for each of the suffering types for a decedent, a non-decedent and a primary family caregiver. Our findings of the types, severity, frequency and duration of suffering associated with cervical cancer should inform global, regional, national and local health care strategic planning so that the health investments can be better aligned with the needs.